2021
DOI: 10.1200/jco.20.02636
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit for Individuals With Constitutional Mismatch Repair Deficiency Undergoing Surveillance

Abstract: PURPOSE Constitutional mismatch repair deficiency syndrome (CMMRD) is a lethal cancer predisposition syndrome characterized by early-onset synchronous and metachronous multiorgan tumors. We designed a surveillance protocol for early tumor detection in these individuals. PATIENTS AND METHODS Data were collected from patients with confirmed CMMRD who were registered in the International Replication Repair Deficiency Consortium. Tumor spectrum, efficacy of the surveillance protocol, and malignant transformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 38 publications
3
47
1
1
Order By: Relevance
“…Clinical data (cancer incidence and time) were collected from 106 patients with CMMRD registered in the International Replication Repair Deficiency Consortium [6][7][8][9]12 between 2008 and 2019. Metachronous (arising sequentially and after completion of treatment for the first primary tumor) and synchronous tumors (distinct cancers that either coexist at the time of the original diagnosis or develop during the treatment of the original cancer and/or , 6 months from the primary diagnosis) were identified, and whole-exome sequencing (WES) was preformed from their paired tumor and germline samples to determine TMB, COSMIC mutational signatures, 13 neoantigen burden, and microsatellite (MS)-indels 14 using established tools (Data Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical data (cancer incidence and time) were collected from 106 patients with CMMRD registered in the International Replication Repair Deficiency Consortium [6][7][8][9]12 between 2008 and 2019. Metachronous (arising sequentially and after completion of treatment for the first primary tumor) and synchronous tumors (distinct cancers that either coexist at the time of the original diagnosis or develop during the treatment of the original cancer and/or , 6 months from the primary diagnosis) were identified, and whole-exome sequencing (WES) was preformed from their paired tumor and germline samples to determine TMB, COSMIC mutational signatures, 13 neoantigen burden, and microsatellite (MS)-indels 14 using established tools (Data Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Constitutive mismatch repair deficiency (CMMRD, MIM#276300) is a rare autosomal recessive inherited disease caused by pathogenic variants in one of the mismatch repair genes MLH1 , MSH2 , MSH6 or PMS2 (Bakry et al 2014 ; Wimmer et al 2014 , 2017 ; Suerink et al 2019 ; Perez-Valencia et al 2020 ; Aronson et al 2021 ; Duorno et al 2021 ). Children with CMMRD often have multiple CALM that are similar to those seen in patients with NF1 or Legius syndrome.…”
Section: Differential Diagnosis Of Nf1 Versus Legius Syndrome and Cmmrdmentioning
confidence: 99%
“…Some patients with CMMRD even meet the clinical NIH diagnostic criteria for NF1 (Wimmer et al 2014 ). It is important to distinguish between these conditions because CMMRD is associated with a high risk of childhood malignancy unlike NF1 and Legius syndrome (Bakry et al 2014 ; Wimmer et al 2014 , 2017 ; Suerink et al 2019 ; Perez-Valencia et al 2020 ; Aronson et al 2021 ; Duorno et al 2021 ).…”
Section: Differential Diagnosis Of Nf1 Versus Legius Syndrome and Cmmrdmentioning
confidence: 99%
“…12 Cancer surveillance is essential to improving long-term prognosis, as it promotes early cancer detection and prevention. 13 To prevent carcinogenesis in patients with CMMRD, methodologies such as aspirin intake, which was reportedly effective against LS, and ICI, neoantigen vaccine or a combination thereof have been considered. 4,8,[12][13][14] Chang et al reported that immunoprofiling of premalignant lesions with LS suggested the effectiveness of ICIs.…”
Section: Could the Immune Checkpoint Inhibitor Against Colorectal Can...mentioning
confidence: 99%
“…13 To prevent carcinogenesis in patients with CMMRD, methodologies such as aspirin intake, which was reportedly effective against LS, and ICI, neoantigen vaccine or a combination thereof have been considered. 4,8,[12][13][14] Chang et al reported that immunoprofiling of premalignant lesions with LS suggested the effectiveness of ICIs. 15 This report suggested the efficacy of ICI for the prevention of carcinogenesis from polyps.…”
Section: Could the Immune Checkpoint Inhibitor Against Colorectal Can...mentioning
confidence: 99%